Human body tracking and interactive applications for balance rehabilitation - Andreikanich, Anna-Khrystyna (2019)
In recent years with the development of Virtual Reality and gaming industry, a number of Virtual Reality and Motion tracking devices have been offered on the market for an affordable price. Besides the applications in gaming, Virtual Reality potential in the medical rehabilitation was recognized as well. It offers a new approach to treatment in Stroke and Spinal Cord (SCI) Injury rehabilitation. The aim of this work is a research of the application of VR games in the rehabilitation; Identification of how they can increase the motivation of Spinal Cord Injury and Stroke patients for performing exercises relevant for their recovery. This work was performed in collaboration with the Rovisco Pais Rehabilitation Center. Based on the case study of the rehabilitation center and consultancies with the therapists, a set of mini-games was produced. In the first produced mini-game, the aim was training of the upper limb movements for Stroke patients. The developed game yet, hasn’t been tested because of the lack of the occupational therapists. Therefore, the work continued in the direction of producing the mini-game for gait restoring. However, since the evaluation of the Kinect v2 sensor for motion tracking proved that it doesn’t have enough precision the next game developed was a trunk balance training game. The target audience of the game was SCI patients. The produced game was tested with 9 students and based on the results it was further improved and tested with 6 SCI patients. The testing’s results suggested that these types of games can be helpful in the recovery process of SCI patients and can be motivate the patients for the recovery.